Demographics and the decline in firm entry: Lessons from a life-cycle model - Oke Röhe; Nikolai Stähler (Deutsche Bundesbank, 2020)
Since the mid-1970s, firm entry rates in the United States have declined significantly. This also holds for other OECD countries over the past years. At the same time, these economies experienced a gradual process of population aging. Applying a tractable life-cycle model with endogenous firm dynamics, we show that falling US firm entry rates can be explained by demographic transition. Specifically, our model simulations suggest that aging can account for up to one third of the observed decrease in US firm entry rates. In addition to the negative effects of a slowdown in working-age population growth on firm entry, our analysis points out that an increase in longevity may also be an important factor contributing to the decline in business dynamism, weighing on both firm entry and exit rates.
Keywords: H25; L52; E20; E62; L10; O30; 330; Life-Cycle model; Population aging; Business dynamism; Firm entry